Inventarisasi Kepadatan Perlintasan Sebidang Kereta Api Berdasarkan Warna Peta Jalan pada Aplikasi Google Maps di Kota Madiun” - Agustinus Prasetyo; Dara Aulia Feryando (Jurnal Syntax Admiration, 2024)
Through this research, it is expected to know the characteristics of the level of traffic density around railway crossings and contribute to improving the safety and efficiency of railway crossings in Indonesia.How is the inventory of vehicle traffic density at railway crossings in Madiun City? Based on the color condition of the highway map in the Google Maps application. The method carried out is to collect historical data on traffic conditions on the google map application at a specified JPL point with a certain period of time, namely during the morning, afternoon and evening rush hours, traffic density condition data is shown with certain color indications. As comparison data, samples of live-traffic data are taken on Google Maps which will be analyzed and identified the level of density of railway crossings. Data analysis was carried out to identify railway crossing points that are prone to congestion in the city of Madiun. Through analysis of railway crossing density data, crossing points that have high, medium and low density levels will be identified. Color condition data shows that the plot crossing on JPL 138 has a frequency percentage of 50.37% and 47.71% of the distance is green, with the level of vehicle traffic density is not dense to rather dense. JPL 138 crossing on the side of Jalan Yos Sudarso – Pahlawan has a higher level of traffic density.